Oral Health Status among Group of Patients with Juvenile Idiopathic Arthritis According to Duration of Illness and Age Group in Iraq - Shallan, Zainab; Al-Rawi, Nadia Aftan (Journal of Baghdad College of Dentistry, 2016)
Background: Juvenile idiopathic arthritis (JIA) is a chronic disease of childhood. Increased prevalence of periodontal disease and dental caries in juvenile idiopathic arthritis is due to difficulties in executing good oral hygiene. This study was conducted to assess oral health status in patients with Juvenile idiopathic arthritis according to age and duration of illness. Materials and methods: A research was conducted among Juvenile idiopathic arthritis patients attending Baghdad Teaching Hospital with different age and both gender, underwent a clinical evaluation of their dental and oral condition. Diagnosis of dental caries was done according to the criteria of WHO (1997). Dental plaque, gingival condition, calculus were assessed by PI/ GI/Cal I following the criteria of Silness and Loe (1964), Loe and Silness (1963), Ramfjord (1959) respectively . Results: The study showed the percentage of caries-free patients was 6.17%. Mean value of caries experience of primary teeth decreased with increasing age while caries experience of permanent teeth increased with increasing age, Pl and Cal indices mean values increased with increase age and difference was found significant. Mean value of dmft decreased with the disease advance and significant difference was found. Caries experience of permanent teeth increase with increase disease duration and difference was significant. Conclusion: The systemic effect of disease may impact on oral health